The Role of Hematological Parameters in Atrial Fibrillation Risk Assessment - Rafaqat, Saira; Sharif , Saima; Naz, Shagufta; Majeed, Mona; Saqib, Muhammad; Farzana Rashid; Ali, Qasim (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Atrial fibrillation (AF) is an irregular and rapid heartbeat in the heart’s atrial chambers. Conversely, haematological parameters are commonly utilized in clinical settings to evaluate overall health and disease. Our research explored the potential role of haematological parameters in atrial fibrillation within the Pakistani population. In this case-control a total of 400 participants were enrolled from the Punjab Institute of Cardiology, Lahore, Pakistan. The participants were divided into two groups: a control group comprising 200 healthy individuals, and an AF group consisting of 200 individuals diagnosed with atrial fibrillation. Haematological parameters were assessed using an automated hematology analyzer. The AF group had higher levels of white blood cells, red blood cells, and mean corpuscular volume as compared to control group. Conversely, lower levels of haemoglobin, hematocrit, mean corpuscular haemoglobin, mean corpuscular haemoglobin concentration and platelets were observed in AF group compared to control group. In conclusion, our research established a significant relationship between haematological parameters and atrial fibrillation in the Pakistani population.